Targeting the A3 adenosine receptor to treat hepatocellular carcinoma: anti-cancer and hepatoprotective effects - Pnina Fishman; Salomon M. Stemmer; Avital Bareket-Samish; Michael H. Silverman; William D. Kerns (Purinergic Signalling, 2023)
The A3 adenosine receptor (A3AR) is over-expressed in human hepatocellular carcinoma (HCC) cells. Namodenoson, an A3AR agonist, induces de-regulation of the Wnt and NF-kB signaling pathways resulting in apoptosis of HCC cells. In a phase I healthy volunteer study and in a phase I/II study in patients with advanced HCC, namodenoson was safe and well tolerated. Preliminary evidence of antitumor activity was observed in the phase I/II trial in a subset of patients with advanced disease, namely patients with Child–Pugh B (CPB) hepatic dysfunction, whose median overall survival (OS) on namodenoson was 8.1 months. A phase II blinded, randomized, placebo-controlled trial was subsequently conducted in patients with advanced HCC and CPB cirrhosis. The primary endpoint of OS superiority over placebo was not met. However, subgroup analysis of CPB7 patients (34 namodenoson-treated, 22 placebo-treated) showed nonsignificant differences in OS/progression-free survival and a significant difference in 12-month OS (44% vs 18%, p = 0.028). Partial response was achieved in 9% of namodenoson-treated patients vs 0% in placebo-treated patients. Based on the positive efficacy signal in HCC CPB7 patients and the favorable safety profile of namodenoson, a phase III study is underway.

Control of tick populations by spraying Metarhizium anisopliae conidia on cattle under field conditions - G. P. Kaaya; M. Samish; M. Hedimbi; G. Gindin; I. Glazer (Experimental and Applied Acarology, 2011)

Protection of Metarhizium anisopliae conidia from ultra-violet radiation and their pathogenicity to Rhipicephalus evertsi evertsi ticks - M. Hedimbi; G. P. Kaaya; S. Singh; P. M. Chimwamurombe; G. Gindin; I. Glazer; M. Samish (Experimental and Applied Acarology, 2008)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)